K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 4 2018

11x(X-6)= (4xX)+11

=> 11X-66= 4X+11

=> 7X= 77

=> X= 11

18 tháng 4 2018

11x(X-6)=(4×X)+11

11×X-6×11=4×X+11

11×X-66=4×X+11

7xX=11+66

7×X=77

X=77:7

X=11

HỌC TỐT

13 tháng 10 2018

\(4.3^{x-1}+2.3^{x+2}=4.3^6+2.3^9\)

\(3^{x-1}.\left(4+2.3^3\right)=3^6.\left(4+2.3^3\right)\)

\(\Leftrightarrow3^{x-1}=3^6\)

\(\Leftrightarrow x-1=6\)

\(\Leftrightarrow x=7\)

Vậy \(x=7\)

13 tháng 10 2018

hai bài mà bn ??

11(6-x)-4x=11

=>66-11x-4x=11

=>66-15x=11

=>15x=66-11=55

=>\(x=\dfrac{55}{15}=\dfrac{11}{3}\)

4 tháng 8 2016

11 x ( X - 6 ) = 4 x X + 11

11 x X - 11 x 6 = 4 x X + 11 

11 x X - 66 = 4 x X + 11

\(\Rightarrow\)X x ( 11 - 4 ) = 66 - 11

        X x 6 = 55

         x = 55 : 6

   x  = 55 /6

1: x=3/4-1/2=3/4-2/4=1/4

2: x-1/5=2/11

=>x=2/11+1/5=21/55

3: x-5/6=16/42-8/56

=>x-5/6=8/21-4/28=5/21

=>x=5/21+5/6=15/14

4: x/5=5/6-19/30

=>x/5=25/30-19/30=6/30=1/5

=>x=1

5: =>|x|=1/3+1/4=7/12

=>x=7/12 hoặc x=-7/12

6: x=-1/2+3/4

=>x=3/4-1/2=1/4

11: x-(-6/12)=9/48

=>x+1/2=3/16

=>x=3/16-1/2=-5/16

21 tháng 7 2023

1)x= 1/4

2)x= 2/11+ 1/5

   x= 21/55

3)x - 5/6 = 5/21

   x         = 5/21+5/6

   x         = 15/14

4)x/5 = 5/6 + -19/30

   x:5 = 1/5

   x    = 1/5.5

   x    = 1

5) |x| - 1/4 = 6/18

    |x|           = 6/18 - 1/4

    |x|            =7/12

⇒x= 7/12 hoặc -7/12

6)x = -1/2 +3/4

   x= 1/4

7) x/15 = 3/5 + -2/3

   x:15  = -1/15

  x        = -1/15. 15

  x        = -1

8)11/8 + 13/6 = 85/x  

       85/24      = 85/x

  ⇒      x           = 24

9) x - 7/8 = 13/12

   x          = 13/12 + 7/8

   x          = 47/24

10)x - -6/15 = 4/27  

     x            = 4/27 + (-6/15)

    x             = -34/135

11) -(-6/12)+x = 9/48

                    x= 9/48 - 6/12

                    x = -5/16

12) x - 4/6 = 5/25 + -7/15

      x -4/6  =  -4/15

     x           = -4/15 + 4/6

    x             = 2/5

24 tháng 3 2022

\(\dfrac{-4}{3}-\dfrac{5}{7}+\dfrac{4}{3}=\left(\dfrac{4}{3}+\dfrac{-4}{3}\right)-\dfrac{5}{7}=0-\dfrac{5}{7}=-\dfrac{5}{7}\)

 

\(\dfrac{3}{13}\cdot\dfrac{6}{11}+\dfrac{3}{13}\cdot\dfrac{9}{11}-\dfrac{3}{13}\cdot\dfrac{4}{11}=\dfrac{3}{13}\cdot\left(\dfrac{6}{11}+\dfrac{9}{11}-\dfrac{4}{11}\right)=\dfrac{3}{13}\cdot1=\dfrac{3}{13}\)

cảm ơn bạn.

14 tháng 8 2023

a) \(...\Rightarrow x.\left(2+5\right)=14\Rightarrow x.7=14\Rightarrow x=14:7=2\)

b) \(...\Rightarrow x.\left(9+1\right)=20\Rightarrow x.10=20\Rightarrow x=20:10=2\)

c) \(...\Rightarrow x.\left(\dfrac{2}{3}+\dfrac{1}{3}\right)=1999\Rightarrow x.\dfrac{3}{3}=1999\Rightarrow x=1999\)

d) \(...\Rightarrow11.x+22=5.x+40\Rightarrow11.x-5.x=40-22\Rightarrow6.x=18\Rightarrow x=18:6=3\)

e) \(...\Rightarrow11.x-66=4.x+11\Rightarrow11.x-4.x=11+66\Rightarrow7.x=77\Rightarrow x=77:7=11\)

f) \(...\Rightarrow\left(3.x-12\right):x=12-10\)

\(\Rightarrow3.x-12=2.x\)

\(\Rightarrow3.x-2.x=12\)

\(\Rightarrow x=12\)

g) \(...\Rightarrow\left(5.x+7\right):x=26-20\)

\(\Rightarrow5.x+7=6.x\)

\(\Rightarrow6.x-5.x=7\)

\(\Rightarrow x=7\)

h) \(...\Rightarrow x.\left(1999-1\right)=1999.\left(1997+1\right)\)

\(\Rightarrow x.1998=1999.1998\)

\(\Rightarrow x=1999.1998:1998\)

\(\Rightarrow x=1999\)

14 tháng 8 2023

a, \(x\times\) 2 + \(x\times\) 5 = 14

   \(x\) \(\times\) ( 2 + 5) = 14

    \(x\) \(\times\) 7 = 14

    \(x\)         = 14: 7

      \(x\)        = 2

b, \(x\times9\) + \(x\)= 20

     \(x\) \(\times\)( 9 + 1) = 20

       \(x\) \(\times\) 10 = 20

       \(x\)          = 2

c, \(x\) : \(\dfrac{3}{2}\) + \(x\times\dfrac{1}{3}\) = 1999

   \(x\times\) \(\dfrac{2}{3}\) + \(x\) \(\times\dfrac{1}{3}\) = 1999

   \(x\times\) ( \(\dfrac{2}{3}\) + \(\dfrac{1}{3}\)) = 1999

    \(x\)                  = 1999

d,   11\(\times\)(\(x+2\)) = 5 \(\times\) \(x\) + 40

     11 \(\times\) \(x\) + 22 = 5 \(\times\) \(x\) + 40

      11 \(\times\) \(x\)        = 5 \(\times\) \(x\) + 40 - 22

       11 \(\times\) \(x\)       = 5 \(\times\) \(x\) + 18

        11 \(\times\) \(x\)     - 5 \(\times\) \(x\) = 18

         \(x\) \(\times\) ( 11 - 5) = 18

           \(x\) \(\times\) 6 = 18

            \(x\)        = 3

 

AH
Akai Haruma
Giáo viên
23 tháng 7 2023

Lời giải:

1.

$3^{x+2}+4.3^{x+1}=7.3^6$

$3^{x+1}.3+4.3^{x+1}=7.3^6$

$3^{x+1}(3+4)=7.3^6$

$3^{x+1}.7=7.3^6$

$\Rightarrow 3^{x+1}=3^6$

$\Rightarrow x+1=6$

$\Rightarrow x=5$

2.

$5^{x+4}-3.5^{x+3}=2.5^{11}$

$5^{x+3}.5-3.5^{x+3}=2.5^{11}$

$5^{x+3}(5-3)=2.5^{11}$

$2.5^{x+3}=2.5^{11}$

$\Rightarrow 5^{x+3}=5^{11}$

$\Rightarrow x+3=11$

$\Rightarrow x=8$

3.

$4^{x+3}-3.4^{x+1}=13.4^{11}$

$4^{x+1}.4^2-3.4^{x+1}=13.4^{11}$

$4^{x+1}.16-3.4^{x+1}=13.4^{11}$

$13.4^{x+1}=13.4^{11}$

$\Rightarrow 4^{x+1}=4^{11}$

$\Rightarrow x+1=11$
$\Rightarrow x=10$

Bài 1:

a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)

b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)

c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)

d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)

hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)

e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)

hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)

27 tháng 7 2023

dad